Orbital lesion (pseudotumor and dacryoadenitis) is a manifestation of systemic sarcoidosis - E.A. Burylova; L.A. Mamaeva; A.S. Berdnikova; O.K. Fedorova (РМЖ "Клиническая офтальмология")
E.A. Burylova, L.A. Mamaeva, A.S. Berdnikova, O.K. Fedorova Ural Scientific Research Institute of Phtysiopulmonology — Branch of the National Medical Research Center of Phtysiopulmonology, Yekaterinburg, Russian Federation Abstract Ocular manifestations of systemic sarcoidosis may emerge at any disease stage. Ocular sarcoidosis is typically characterized by uveitic presentations that predominantly involve the choroid of anterior eye segment. However, orbital pseudotumor, dacryoadenitis, and other rare presentations (optic neuritis, dacryocystitis etc.) also occur in sarcoidosis. Threatened vision loss and poor quality of life are the reasons to prescribe systemic steroids in generalized sarcoidosis. Chest CT is required to identify respiratory diseases when sarcoidosis manifests as uveitis or granulomatous orbital inflammation. Multidisciplinary diagnostic and treatment approach to suspected sarcoidosis provides timely verified diagnosis and management strategy. This paper addresses case report of systemic sarcoidosis in a 34-year-old man. The initial manifestation was vision loss and left orbital pseudotumor. The enlarged subclavian lymph node and its biopsy were suspicious of granulomatous inflammation. Chest CT identified disseminated pulmonary lesions and intrathoracic lymphadenopathy that are typical of sarcoidosis. The results of multidisciplinary examina tions verified systemic sarcoidosis. Systemic steroids resulted in clinical and radiological improvement and medicinal regression of the disease. Keywords: sarcoidosis, orbital pseudotumor, dacryoadenitis, adenopathy, computed tomography, multidisciplinary approach. For citation: Burylova E.A., Mamaeva L.A., Berdnikova A.S., Fedorova O.K. Orbital lesion (pseudotumor and dacryoadenitis) is a manifestation of systemic sarcoidosis. Russian Journal of Clinical Ophthalmology. 2021;21(1):40–44. DOI: 10.32364/2311-7729-2021-21-1-40-44.